Penggunaan Media Colored Stick Untuk Meningkatkan Pemahaman Konsep Operasi Hitung Penjumlahan dan Pengurangan Bilangan Bulat Pada Siswa Sekolah Dasar Kelas III - Siti Hanifatul Aziz; Fatkhul Arifin (Elementar : Jurnal Pendidikan Dasar, 2021)
This study aims to improve the understanding of the concept of arithmetic operations of addition and subtraction of integers in class IV at SDN Jampang 03 through the use of colored stick media. The research method used is Classroom Action Research (CAR), adapting the Kemmis and Mc.Taggart. Subjects in this study consisted of 29 students in class IV at SDN Jampang 03. The results of this study showed that there was an increase in students' conceptual understanding after the application of colored stick learning media in mathematics subjects for arithmetic operations on addition and subtraction of integers. This can be seen from the increase in the average score of the research instrument in the first cycle of 72.45% which increased in the second cycle to 94.36%. The conclusion of this study is that the use of colored stick media can improve the understanding of the concept of arithmetic operations of addition and subtraction of integers in class IV at SDN Jampang 03.Keywords : Colored Stick Learning Media, Concept Understanding, Operation Counting Addition and Subtraction of Integer